Mechanisms of NLRP3 inflammasome in pathogenesis and progression of inflammation-related gastrointestinal diseases - Fengmei Liu; Bozong Shao; Yaqin Zhu; Xiaochun Xue; Xiaoyan Wu (PeerJ)
The inflammasome is a novel component of the innate immune response. It plays a crucial role in the pathogenesis and progression of inflammation-related gastrointestinal diseases. Among various inflammasomes, the NLR family pyrin domain containing 3 (NLRP3) inflammasome is one of the most extensively studied. Increasingly, researchers are exploring its roles and mechanisms, particularly in inflammation-immune-related diseases. As a result, a review paper is demanded to review and summarize the previous and latest studies on the role and mechanisms of NLRP3 inflammasome in pathogenesis and progression of inflammation-related gastrointestinal diseases. This review comprehensively elaborates on the biological characteristics of the NLRP3 inflammasome, including its assembly and activation mechanisms. Additionally, it emphasizes the roles and mechanisms of the NLRP3 inflammasome in common inflammation-related gastrointestinal diseases such as ulcerative colitis, Crohn’s disease, pancreatitis, and non-alcoholic fatty liver disease (NAFLD). Furthermore, the application of NLRP3 inflammasome inhibitors in treating these diseases is discussed. Articles from PubMed and Web of Science on NLRP3 inflammasome, ulcerative colitis, Crohn’s disease, pancreatitis, and NAFLD were summarized to analyze the data and conclusions carefully to ensure the comprehensiveness, completeness, and accuracy of the review. This study aims to provide scholars engaged in research on gastrointestinal diseases with new directions for developing more effective therapeutics for inflammation-related gastrointestinal diseases by investigating the NLRP3 inflammasome’s role in these conditions.